An empirical investigation of the relationship between individual learner factors and foreign language speaking anxiety in EFL university learners - Malik, Sameena; Oteir, Ibrahim; Alotaibi, Abdullah Nijr (International Journal of Innovative Research and Scientific Studies, 2024)
The current study recruited 306 participants (males=194, females= 112) to fill out a questionnaire consisting of two sections for demographic information and a second section with 38 close-ended items to investigate the structural relationships among individual learner factors and anxiety when speaking a foreign language in Chinese EFL university learners. These factors included exposure to English, attitude towards learning English, perceived oral proficiency, years of learning English, perceived effectiveness of the use of social media, perceived competence and parental education status. The findings of the direct effects indicated that exposure to English, attitude towards learning English and perceived oral proficiency were negatively correlated whereas years of learning English and the perceived effectiveness of social media had an insignificant effect on foreign language speaking anxiety. In addition, according to the indirect predictive effects of perceived competence (mediator) on foreign language speaking anxiety, all other factors with the exception of years of learning English were found to be positively mediated by perceived competence. Lastly, the moderating effect of parental education status indicated that the interaction term (perceived competence x parental education status) had a negative and significant effect on foreign language speaking anxiety. The findings indicate that speaking anxiety exists in and out of class and can cause a detrimental effect on university learners’ communication and speaking skills due to a lack of confidence, practice, exposure and interaction. This research provides several insightful practical implications for EFL teachers and policymakers.